Changes in corneal innervation and pain responses in fungal keratitis - Chang-Jie Ren; Yi-Fan Zhou; Yuan Wu; Xu-Dong Peng; Cui Li; Qian Wang; Guo-Qiang Zhu; Jia You; Jie Zhang; Gui-Qiu Zhao; Jing Lin (International Journal of Ophthalmology, 2020)
AIM: To characterize changes in the cornea nerve and pain responses in fungal keratitis (FK). METHODS: A retrospective analysis of in vivo confocal microscopy images of 11 FK corneas was performed, and the results were compared with those for 11 normal corneas. Subbasal corneal nerves were analyzed for total nerve number, main nerve trunk number, branching patterns and tortuosity. C57BL/6 mice were infected with Aspergillus fumigatus. Disease severity was determined through clinical scoring and slit lamp photography. Corneas were harvested at 1, 3, 5, and 7d post infection (p.i.) and assessed for β III tubulin. Corneal mechanical sensitivity thresholds were detected by von Frey test. β-endorphin (β-EP) and μ receptor protein expression was detected through Western blotting. RESULTS: Total nerve number, main nerve trunk number, and nerve branching were significantly lower in FK patients than in controls, but tortuosity was not significantly different. In infected mice, subbasal nerve density decreased from 1d p.i., reaching a minimum at 5d p.i. Clinical scores rose at 1d p.i., peaked at 3d p.i., and decreased at 5d p.i. Mechanical sensitivity thresholds showed the same trends. β-EP and μ receptor protein expression increased after infection. CONCLUSION: Corneal nerve density is lower in FK patients and Aspergillus fumigatus-infected mice than in controls. Pain sensitivity decreases with postinfection corneal ulcer aggravation. β-EP and μ receptor proteins are both upregulated in infected mouse corneas.